Plan de Negocios para comercializar Lubricantes Golden Bear Rev Oil Api Ck-4 en las cooperativas de transporte urbano de la ciudad de Guayaquil. - Celleri León, Víctor Gerónimo (2019)
Currently companies must understand the behavior of the customer to obtain a market share. In the city of Guayaquil, the transport sector plays a very important role due to the transfer of citizens from one place to another and is affected by roads, climatic conditions among other factors. Therefore, it is necessary to maintain the engines in optimal conditions and in turn represents a business opportunity in the sale of a car lubricant for the maintenance of transport. The general objective of this sales plan is to position the sale of lubricants in the transport sector of the product Rev Oil Api CK -4 of the city of Guayaquil, year 2020. The market and company study was carried out where 100 surveys were applied to the carriers that work in the city of Guayaquil. To analyze the information, quantitative techniques were used. The results were favorable for the acceptance of the new product.